High-activity Cu nanowires electrocatalysts for CO2 reduction. (July 2017) - Huang, Peng; Ci, Suqin; Wang, Genxiang; Jia, Jingchun; Xu, Jiangwei; Wen, Zhenhai
Abstract: The daunting challenge in electrochemical conversion of CO2 into carbon resource is to explore high-activity and high-selectivity electrocatalysts for CO2 reduction reaction (CO2 RR). Here, we report a water-bath route for tunable synthesis of a set of CuO nanostructures including nanowires (NWs), microsphere and nanoflake. The CuO NWs show a unique one-dimensional (1D) structure constructed by nanoparticles building block and manifest a significantly enhanced electrochemical surface area compared with the counterparts and the bulk CuO. Systematic electrochemical studies demonstrate the CuO NWs, as electrocatalyst of CO2 RR, manifests a highly electrocatalytic activity, as demonstrated by reaching a current dentistry of 2 mA cm −2 at a relative low onset potential and delivering a catalytic current density of up to 100 mA cm −2 at −1.6 V. The nanoparticles assembled 1D structure provides a large amount of edge active sites and thus contributes to such a high electrocatalytic activity. Besides a small quantity of HCOOH, the major products of CO2 RR are H2, CO, with tunable ratio of H2 /CO in the range of 1.75:1 to 2.75:1 depending on the applied potential; such H2 /CO mixture product are potentially used for the syngas that are key feedstocks to produce a variety of liquid fuels in industry.